Prolonged mechanical systole and increased arterial wave reflections in diastolic dysfunction. Issue 11 (18th May 2006) - Weber, T; Auer, J; O'Rourke, M F; Punzengruber, C; Kvas, E; Eber, B
Abstract : Objective: To evaluate whether left ventricular ejection time indexed for heart rate (left ventricular ejection time index (LVETI)) and arterial wave reflections (augmented pressure (AP)) are increased in patients with diastolic dysfunction (DD). Design: Prospective observational study. Setting: University teaching hospital providing primary and tertiary care. Subjects: 235 consecutive patients undergoing left heart catheterisation were categorised as having definite DD, possible DD or no DD (controls) on the basis of their left ventricular end diastolic pressures and N-terminal brain natriuretic peptide concentrations. Main outcome measures: LVETI and AP were prospectively assessed non-invasively by radial applanation tonometry. In addition, all patients underwent comprehensive echocardiography, including tissue Doppler imaging of mitral annulus velocity in early diastole (E′). Results: LVETI was longer in patients with definite DD than in patients with possible DD and in controls (433.6 (SD 17.2), 425.9 (17.9) and 414.3 (13.6) ms, respectively, p < 0.000001). Arterial wave reflections were higher in definite DD than in possible DD and control groups (AP was 19.4 (SD 8.9), 15.2 (8.0) and 10.7 (6.8) mm Hg, respectively, p < 0.000001). In receiver operating characteristic curve analysis, LVETI detected DD as well as echocardiography (E:E′). Area under the curve for LVETI to differentiate patients with definite DD from normal controls was 0.81 (95% CI 0.72 to 0.89, p < 0.0001). In multivariable logistic regression analysis, LVETI added significant independent power to clinical and echocardiographic variables for prediction of DD. Conclusions: Mechanical systole is prolonged and arterial wave reflections are increased in most patients with DD. Rapid non-invasive assessment of these parameters may aid in confirming or excluding DD.